PHYSICAL PROPERTIES OF MEMBRAMO, SUPERWIN, AND CIMELATI RICES - Mustofa Mustofa (Jurnal Technopreneur (JTech), 2020)
Determination of the physical properties of rice is intended to facilitate the processing and handling to produce final product with best quality. These properties include geometry, surface area, volume, density, bulk density, porosity, and angle of repose. Determination of the physical properties of rice in terms of geometry is carried out by measuring length (L), width (W), and thickness (T). The measurement of these parameters uses a digital caliper with an accuracy of 0.01 mm. The volume of rice can be determined based on dimensional parameters. Density, bulk density and porosity of rice were determined by measuring its mass using a digital scale with an accuracy of 0.001 gr and based on the determination of the volume. Angle of repose is determined by spilling rice on the flat surface of a container so that the height (h) of the pile of rice and the diameter (D) is known. Based on the research results, it is known that the geometry of Membramo, Superwin, and Cimelati rices does not have a significant difference, in fact there are similarities in the eccentricity aspect, where all three have the same value, namely 0.96. The average surface area value of Cimelati rice is greater than that of Membramo and Superwin rice, as well as its volume. The average of surface area and volume of Cimelati rice were 23.89 mm2 and 13.41 mm3, respectively. Meanwhile, Superwin rice has the largest individual and bulk densities, 1.42 gr/cm3 and 0.80 gr/cm3, respectively. In addition, Superwin and Cimelati rices have the lowest porosity and angle of repose, namely 40.69% and 26.59o.